(untitled) (Jurnal Pendidikan Fisika, 2022)
The distance learning process at the Politeknik Ilmu Pelayaran Makassarrequires cadets to learn more independently when compared to the face-to-face learning process. The purpose of this study was to determine the effect of learning independence and learning motivation on the learning outcomes of applied physics during the distance learning process. This studyis ex-post facto research. The research was carried out at the Politeknik Ilmu Pelayaran Makassarin April – June 2021 with a research sample of 207 cadets. Data was collected using documentation and questionnaire methods and analyzed using regression and correlation analysis.The results showed that there was an influence of motivation on the learning outcomes of cadets in the implementation of distance learning at the Politeknik Ilmu Pelayaran Makassarwith a correlation coefficient of 0.216. Likewise, the learning independence of cadets’ learning outcomes in the implementation of distance learning at the Politeknik Ilmu Pelayaran Makassarwith a correlation coefficient of 0.681. The conclusion obtained is learning independent and motivation have an effect on learning outcomes.